The Indigenous Voice in Mukarung’s Damini Bhir and Subba’s Lato Pahad: Quest for Justice and Identity - Khadka, Kul Bahadur (Tribhuvan University Journal, 2025)
This research aims to explore the indigenous voices embedded in Rajan Mukarung’s Damini Bhir and Upendra Subba’s Lato Pahad and investigates the factors influencing the indigenous integrity and identity. The voices, both heard and hidden, are based on the indigenous epistemologies and they advocate justice, parity and solidarity for indigenous identity, specifically diverse identity of the Rai and Limbu communities in the eastern hilly region of Nepal. The study of the indigenous voices can significantly help promote humanity and kinship, and moreover, it can awaken the state power to hear the marginalized voices for a justifiable society. The research employs indigenous perspectives based on Native American theorists Chadwick Allen’s trans-indigenous insights, Daniel Heath Justice’s kinship phenomena and Jace Weaver’s concepts of communities. Various existing scholarships and the primary texts have been analytically consulted for the consolidation of the research. The research reveals indigenous people’s activism, resilience and mutuality which can promote a pan-indigenous vision. The Rai and Limbu communities adhere to the indigenous phenomena of memory, spirituality, kinship and reciprocity, and shared identity.